2017
DOI: 10.1021/acs.jpcc.7b02957
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structure Dependence of the Dry Dehydrogenation of Alcohols on Cu(111) and Cu(110)

Abstract: The non-oxidative dehydrogenation of alcohols is considered as an important method to produce aldehydes for the chemical industry and hydrogen gas. However, current industrial processes are oxidative, meaning that the aldehydes are formed along with water, which, in addition to being less energy efficient, poses separation problems. Herein the production of aldehydes from methanol and ethanol on clean and dry Cu(111) and Cu(110) surfaces was investigated in order to understand the catalytic anhydrous dehydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(92 citation statements)
references
References 33 publications
5
86
0
Order By: Relevance
“…34−36 Wachs et al 35 found that C−H bond activation is the rate-determining step in ethanol dehydrogenation. In a recent study, Sykes and co-workers 38 used a combination of temperature-programmed experiments and scanning tunneling microscopy on Cu(111) and Cu(110) model surfaces to verify the two-step dehydrogenation of alcohols. Furthermore, they confirmed that dehydrogenation occurs at defect sites.…”
Section: Resultsmentioning
confidence: 99%
“…34−36 Wachs et al 35 found that C−H bond activation is the rate-determining step in ethanol dehydrogenation. In a recent study, Sykes and co-workers 38 used a combination of temperature-programmed experiments and scanning tunneling microscopy on Cu(111) and Cu(110) model surfaces to verify the two-step dehydrogenation of alcohols. Furthermore, they confirmed that dehydrogenation occurs at defect sites.…”
Section: Resultsmentioning
confidence: 99%
“…96,111,112 On metal oxides with acid-base pairs, the literature suggests that acetaldehyde is formed by a sequential mechanism that begins with the dissociation of ethanol into a surface ethoxy intermediate followed by the E2 or E1cb-elimination of a proton (Scheme 4(a)). 100,[113][114][115][116] According to Sykes et al, acetaldehyde formation occurs similarly on defective Cu, 117 suggesting that this mechanism is not limited to metal oxides. Surface ethoxy species were also detected on other transition metal oxide catalysts during IR-TPSR experiments with ethanol, leading to similar conclusions.…”
Section: Ethanol Dehydrogenationmentioning
confidence: 99%
“…In order to model the reactivity of SAAs, Sykes and coworkers have proposed a mechanistic pathway in which the O-H bond of ethanol is activated first on the SAA surface followed by the α-C-H bond, resulting into the formation of acetaldehyde. 23 The hypothesis is derived from the experiments on the model Cu (111) surface, 24,25 where the O-H bond is observed to activate at a significantly low (160 K) temperature. Our group has developed a comprehensive ab initio MKM to understand ethanol decomposition and dehydrogenation reactions on transition metal surfaces, including all possible mechanistic routes such as O-H, α-C-H, C-C, and C-O activation in ethanol.…”
Section: Introductionmentioning
confidence: 99%